Dental calculus reveals potential respiratory irritants and ingestion of essential plant-based nutrients at Lower Palaeolithic Qesem Cave Israel. (4th April 2016) - Hardy, Karen; Radini, Anita; Buckley, Stephen; Sarig, Rachel; Copeland, Les; Gopher, Avi; Barkai, Ran
Abstract: Reconstructing detailed aspects of the lives of Lower Palaeolithic hominins, who lived during the Middle Pleistocene, is challenging due to the restricted nature of the surviving evidence, predominantly animal bones and stone tools. Qesem Cave, Israel (420–200 ka) is a site that has produced evidence for a wealth of innovative features including controlled use of fire, represented by a repeatedly used hearth. Numerous charred bone and stone tools as well as wood ash have been found throughout the ten metres of archaeological deposits. Here, we describe the presence of a range of potentially inhaled, and ingested, materials extracted from samples of dental calculus from the Qesem Cave hominins. These finds offer an insight into the environment in and around the cave, while micro-charcoal highlights the need for smoke management in enclosed environments. Plant fibres and a phytolith may be evidence of oral hygiene activities or of using the teeth to work raw materials. Starch granules and chemical compounds provide a direct link to ingested plant food items. This extends the evidence for consumption of plant foods containing essential nutrients including polyunsaturated fatty acids and carbohydrates, into the Lower Palaeolithic. Together, these results represent a significant breakthrough towards a better understanding of Middle Pleistocene dietary breadth and highlight some of the challenges facing the adoption of the habitual use of fire for cooking by the Qesem Cave hominins, as well as offering an insight into their ecological knowledge and technological adaptability.